MANIFESTASI SEJARAH PEMIKIRAN EKONOMI ISLAM PADA MASA KHULAFAUR RASYIDIN - Kusuma, Febri; Zahwa, Ersa Amara (Al-Hasyimiyah: Jurnal Ekonomi Syariah, 2024)
The development of Islamic economic principles carried out by the Khulafaur Rasyidin (632 CE–661 CE) represents a significant phase in the history of Islamic economic thought. During the leadership of Abu Bakr As-Siddiq, Umar bin Khattab, Uthman bin Affan, and Ali bin Abi Talib, various economic innovations were introduced, such as zakat distribution, the management of Baitul Mal, a fair taxation system, and land ownership regulation. This study aims to explore the economic policies of that period, their relevance to contemporary economic challenges, and how principles of social justice, transparency, and the balance between state and market applied during that era can inspire modern economic systems, particularly in the context of Indonesia. The research seeks to delve deeper into the economic thought and policies of that time and their relevance to contemporary economic issues. A qualitative method with a historical-descriptive approach was employed. This approach was chosen to analyze and describe the development of Islamic economic thought during the Khulafaur Rasyidin era chronologically and systematically. The results of the study show that several policies of the Rashidun Caliphs were implemented through enforcing zakat laws and using them as instruments for income redistribution, applying trade contracts in accordance with Islamic Sharia principles, accurately managing and calculating zakat, and improving the administration of Baitul Mal. In conclusion, the legacy of Islamic economic thought from the Khulafaur Rasyidin era can make a significant contribution to the development of a more just, ethical, and sustainable economic system in the modern era.